Calculation of Absorbed Dose Distribution for Breast Brachytherapy Simulation By CS-1 131Cs Seed and ADVANTAGETM 103Pd Seed Using Monte Carlo N Particle Extended Simulator - Faisal Reza Rahmat; Mondjo Mondjo; Alexander Agung (Indonesian Journal of Physics and Nuclear Applications, 2017)
Simulation using Monte Carlo code has been conducted to determine the distribution of absorbed dose to the breast brachytherapy with 131Cs and 103Pd radionuclide sources. Simulations performed on stage I breast cancer with cancer diameter is 2 cm. Sources of radionuclides simulated in the form of seed is modeled with CS-1 which is made by IsoRay 131Cs and seed ADVANTAGETM103Pd which is made by IsoAID, LLC. Seed was planted in breast cancer cells. Calculation of absorbed dose distribution was performed by varying the distance from the seed. Variations of the distance started from a radius of 0.3 cm to 2 cm with a range of 0.1 cm respectively. In this simulation will also be reviewed the value of absorbed dose for healthy cell like breast, sternum, and lung. The relation between the absorbed dose and the distance from the seed can be described in the form of power law. The results of the calculation show that the maximum absorbed dose is in the target site of the cancer cells (5.791 ± 0.002) Gy per 5 MBq of 131Cs and (2.755 ± 0.009) Gy per 5 MBq for 103Pd. The absorbed dose at sternum (1.514 ± 0.011) x 10-4 Gy per 5 MBq of 131Cs and (7.515 ± 0.633) x 10-7 Gy per 5 MBq for 103Pd. While the absorbed dose in the lungs is and (3.615 ± 0.082) x 10-5 Gy per 5 MBq for 131Cs and (3.972 ± 0.591) x 10-8 Gy per 5 MBq for 103Pd.